Evaluating role of parity in progress of labour and its outcome using modified WHO partograph - Shah, Nupur; Maitra, Nandita; Pagi, S. L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The progress of labour and its outcome differ based on the parity. These can be graphically proven by using an inexpensive tool -the modified WHO partograph. The plotting also helps to early recognition and prevention of the complications of labour. The objective of the study was to study and compare the course of labour and its outcome in primigravidae and mutigravidae using a graphical tool-Modified WHO partograph. Methods: The study was undertaken at SSG hospital, Baroda from August 2012 to July 2013. One hundred twenty four primigravidae and 124 multigravidae women were recruited according to defined inclusion and exclusion criteria. The progress of labour in active stage was assessed and plotted on Modified WHO partograph. The outcomes studied were: duration of active first stage and second stage, cervicometric progress, Incidence of labour augmentation, Incidence of operative delivery and neonatal outcome (Apgar score, NICU stay and birth weight). Results: The duration of active first stage (5.07 hrs) and second stage (33.57 min) was longer in primigravidae with a slower progress of labour as plotted on the Modified WHO partograph, than in multigravidae (3.78 hrs and 22.86 min respectively). The cervical dilatation rate in primigravidae was 1.22 ± 0.287 cm/hr which was slower than that of multigravidae (1.65 ± 0.408 cm/hr). There was also a higher rate of operative delivery in primigravidae (16.93% vs 3.22%). Conclusions: The results highlight that the modified WHO partograph worked as a useful tool in our population in comparing the progress of labour.